Social implications and workforce issues in the oral health of an ageing population. (March 2015) - Wright, FAC
Abstract: A functional and socially acceptable level of oral health is an integral part of healthy ageing! More teeth, more sophisticated dental technology and increasing co‐morbidities of an ageing Australian society will have significant impacts on oral health professionals and their capacities to work within expanded teams of health, education and social organizations. Society is adapting its perspective on the social role of older citizens; replacing its perception of the elderly as an economic social burden, to one of senior citizens as being a respected and active source of social and economic benefit. Maintaining general and oral health for older Australians will bring into sharp focus the need for recognizing and managing not only the biological markers associated with ageing and frailty, but also the potential mediators on health outcomes associated with changing health and social behaviours. Increasing social capital of older Australians through national policy initiatives such as the Living Longer Living Better reforms, and greater involvement of allied health and carers' organizations in oral health education and health promotion will set a new scene for the roles of dental professionals. Issues of equity will drive the service delivery agenda, and a socio‐cultural shift to 'consumer‐directed' health outcomes will shape the range of services, quality of care and support required by an older Australian population. Formal education and training modules for aged care workers, allied health practitioners and geriatricians will develop. The challenge for the dental profession is the coordination and integration of these changes into new models of dental and general health care.